Referensi Kunci, State of the Art, dan Novelty dalam Pelaksanaan Penelitian Bahasa - Bajuri, Muhammad Zahrul Jihadurrohim; Rahman, Fauzi; Mawaidi, Mawaidi; Prawira, Mentari Putrirahayu (Nitisara: Jurnal Ilmu Bahasa, 2024)
In carrying out research, the role of reference sources, previous research, and research novelty are fundamental and cannot be separated. However, problems arise when in writing, these three elements cannot be described optimally so that the flow of the research problem, research urgency, reference sources and methods used cannot be formulated optimally. Therefore, this article will explain the definitions and concepts of key references, state of the art, and novelty. This study will use the literature review method by analyzing various types of literature sources that are relevant to the topic of discussion. The results of the study show that key references mean the main reference sources used by researchers (key books). State of the Art means the process of identifying previous research to look for gaps. Lastly, research novelty means that a researcher must be able to make research findings or novelty.